PENERAPAN TEKNIK DESENSITISASI SISTEMATIS UNTUK MEREDUKSI KECEMASAN SISWA MENGHADAPI PRAKTIK KERJA LAPANGAN (PKL) - Dwi Sri Rahayu (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
PKL is an activity that must be done by SMK students. However, not every student is able to pass the PKL period smoothly. The unpreparedness of students to face PKL becomes a stressor for these students, causing anxiety. If this anxiety is not immediately addressed, it will ultimately have an impact on student performance that is not optimal. This study aims to determine the effectiveness of the systematic desensitization technique in reducing student’s anxiety facing PKL. This research method uses the One-group Pretest-Posttest Design. The sampling technique used in this research is purposive sampling technique or a purposive sampling technique. To test the hypothesis, the data were analyzed using the Wilcoxon analysis technique. 25.90. Based on the calculation, the Z score is -2.807, while Asymp. Sig. (2-tailed) of 0.005 (p<0.05). The average score of anxiety facing PKL in Catholic Pharmacy Vocational School Bina Farma Madiun after being given systematic desensitization techniques decreased from 25.90 to 14.90. The conclusion is that the application of systematic desensitization techniques is effective in reducing student anxiety in dealing PKL.